ROLE OF SERVANT LEADERSHIP IN ACHIEVING AND DEVELOPING EMPLOYEE’S CAREER SATISFACTION AND INTENTION TO REMAIN WITH THE ORGANIZATION: AN EMPIRICAL STUDY OF TOURIST COMPANIES IN ERBIL CITY, KURDISTAN REGION OF IRAQ. - Sadq, Zana Majed; Faeq, Dalia Khalid; Abdulla, Daroon (Ecoforum Journal, 2021)
This paper aims to study the role of servant leadership in achieving along with developing employee’s career satisfaction and intention to continue with the organization in the tourist companies in Iraqi Kurdistan Region the city of Erbil. This paper has find out that there is a positive correlation and significant effect of servant leadership on career satisfaction along with employee’s intention to continue with the organization. This paper provides a set of recommendations, based on the findings, such as organizations have to make sure that all managers and supervisors are obliged to the style of servant leadership. This would play an important role in rising the degree of job satisfaction of workers and the purpose of remaining with the company.